2020
DOI: 10.1093/cid/ciz1212
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of a Pharmacogenomic Test for Stratified Isoniazid Dosing in Treatment of Active Tuberculosis

Abstract: Background There is marked interindividual variability in metabolism and resulting toxicity and effectiveness of drugs used for tuberculosis treatment. For isoniazid, mutations in the N-acetyltransferase 2 (NAT2) gene explain >88% of pharmacokinetic variability. However, weight-based dosing remains the norm globally. The potential clinical impact and cost-effectiveness of pharmacogenomic-guided therapy (PGT) are unknown. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Because patients with TB harboring NAT2 * 5, * 6, and * 7 show much slower N-acetylation than patients homozygous for NAT2 * 4 (Mthiyane et al, 2020), accumulation of INH and hydrazine occurs in SAs, leading to a higher risk of liver injury (An et al, 2018;Brewer et al, 2019). These phenotypes may be the most efficient pharmacogenomics biomarkers for predicting the risk of ATDILI (Azuma et al, 2013;Mushiroda et al, 2016;Wattanapokayakit et al, 2016;Yuliwulandari et al, 2016;Suvichapanich et al, 2019) and may lead to identification of a cost-effective treatment for TB (Rens et al, 2020). Therefore, categorization of patients as RAs, IAs, and SAs may be useful for treatment with NAT2 substrates (Rens et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because patients with TB harboring NAT2 * 5, * 6, and * 7 show much slower N-acetylation than patients homozygous for NAT2 * 4 (Mthiyane et al, 2020), accumulation of INH and hydrazine occurs in SAs, leading to a higher risk of liver injury (An et al, 2018;Brewer et al, 2019). These phenotypes may be the most efficient pharmacogenomics biomarkers for predicting the risk of ATDILI (Azuma et al, 2013;Mushiroda et al, 2016;Wattanapokayakit et al, 2016;Yuliwulandari et al, 2016;Suvichapanich et al, 2019) and may lead to identification of a cost-effective treatment for TB (Rens et al, 2020). Therefore, categorization of patients as RAs, IAs, and SAs may be useful for treatment with NAT2 substrates (Rens et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These phenotypes may be the most efficient pharmacogenomics biomarkers for predicting the risk of ATDILI (Azuma et al, 2013;Mushiroda et al, 2016;Wattanapokayakit et al, 2016;Yuliwulandari et al, 2016;Suvichapanich et al, 2019) and may lead to identification of a cost-effective treatment for TB (Rens et al, 2020). Therefore, categorization of patients as RAs, IAs, and SAs may be useful for treatment with NAT2 substrates (Rens et al, 2020). Although many studies have reported strong associations of each NAT2 genotype, such as NAT2 * 6A/ * 6A, with the risk of ATDILI (Suvichapanich et al, 2018;Nicoletti et al, 2020;Yuliwulandari et al, 2021), little information is available regarding the associations between NAT2 genotype and the risk of the adverse reactions induced by other NAT2 substrate drugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 4, standard weight-based INH therapy for TB results in over 40% of patients experiencing treatment toxicity and over 30% of patients experiencing treatment failure in populations across the world. Using a robust analysis model of TB treatment costs, Rens and coworkers [89] document that pharmacogenomics-guided therapy is highly cost-effective even with conservative estimates of its impact on INH-induced liver injury and response to therapy.…”
Section: Pharmacogenomic-guided Isoniazid Therapy For Treatment Of Tbmentioning
confidence: 99%
“…Estimated frequency of treatment failure and toxicity of INH treatment for tuberculosis in populations across the world.Adapted from[89].…”
mentioning
confidence: 99%